Quenching and partitioning heat treatment in ductile cast irons - Da Silva A.J.S.T. (2014)
© 2014.A commercial ductile iron alloy was submitted to a quenching and partitioning heat treatment. Samples were austenitized at 900 °C for two hours, quenched at 160 °C and kept at this temperature for 2 minutes and finally were re-heated at temperatures between 300 and 450 °C during time intervals between 2 and 180 minutes. The microstructural evaluation was performed with SEM and X-ray diffraction and the mechanical properties were measured using tensile strength and Charpy tests. In general, the quenching and partitioning treatment is viable to achieving expressive fractions of retained austenite in ductile cast irons. Generally, higher partitioning temperatures produce a higher fraction of retained austenite after shorter times. This behavior can be explained by the increase on diffusion rate of carbon at higher temperatures. For all tested conditions it was possible to see a well-defined process window and the combination of mechanical properties is very similar to the austempered ductile irons.